Optimal generation capacity mix in microgrid to meet demand - Lata Gidwani; Virendra Sharma; Piyush Kumar Choubey; Amit Kumar (Institute of Advanced Engineering and Science, 2021)
This paper presents an approach for optimal generation capacity mix to fulfill future power demand using a micro-grid model which is operated in both the on-grid and off-grid modes. This is achieved using the solar photovoltaic (PV) system, fuel-cell, and battery energy storage system (BESS) with and without the grid-connected mode. Different control approaches and optimal size of the generators are presented. Proposed micro grid with solar PV system, solid oxide fuel cell (SOFC) and back scattered electron detector (BESD) is tested for different operational scenarios of loads. Comparative index of performance (CIP) is introduced to indicate effectiveness of the micro-grid operations in the off-grid mode. This is based on difference in the total harmonic distortions (THD) in both the on-grid and off-grid modes. This is established that CIP indicates that the micro-grid works efficiently in the both the on-grid and off-grid modes during the simulated events of the switching ON/OFF the loads at different test conditions. The optimal generation mix successfully met the load demand with and without grid having conventional generation.